1994
DOI: 10.3109/00498259409043246
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of 2-ethylhexanol administered orally and dermally to the female Fischer 344 rat

Abstract: 1. Excretion balance studies were conducted with 2-ethylhexanol (2-EH) in female Fischer 344 rats following single high (500 mg/kg) and low (50 mg/kg) oral doses of [14C]2-EH, following repeated oral dosing with unlabelled 2-EH at the low level, following dermal exposure for 6 h with a 1 g/kg applied dose of [14C]2-EH, and following a 1 mg/kg i.v. dose of [14C]2-EH. 2. The high, low and repeated low oral dose studies with 2-EH showed similar excretion balance profiles of [14C], with some evidence of metabolic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 6 publications
0
16
0
Order By: Relevance
“…Disposition of 2-EH has been well described; both parent and metabolites are excreted in urine (Deisinger et al, 1994). Inhalation exposure studies found exposure to 120 ppm of 2-EH for 6 h per day for 90 days resulted in no adverse effects (Klimisch et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Disposition of 2-EH has been well described; both parent and metabolites are excreted in urine (Deisinger et al, 1994). Inhalation exposure studies found exposure to 120 ppm of 2-EH for 6 h per day for 90 days resulted in no adverse effects (Klimisch et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Minor urinary components were 2-heptanone and 4-heptanone. In addition, 2-ethyl-delta 5 -hexenoic acid and lactones of 5-hydroxy-2-EHA were also observed, but possibly these might be analytical artefacts, at least in part (Deisinger et al, 1994).…”
Section: Flavouring Group Evaluation 4: 2-ethylhexyl Derivatives Frommentioning
confidence: 99%
“…In addition, 1 mg/kg bw 1-14 C-2-EHol was also given as intravenous (i.v.) injection (Deisinger et al, 1994). Excretion products, including conjugates and exhaled radioactivity, were studied to draw up the excretion balance and, for the oral studies, to describe metabolic pattern.…”
Section: Flavouring Group Evaluation 4: 2-ethylhexyl Derivatives Frommentioning
confidence: 99%
“…If the methyl group is located at an odd-numbered carbon such as the 3-position, beta-oxidation is inhibited and omega-oxidation predominates, primarily leading to polar, acidic metabolites capable of being excreted in the urine as such or as conjugates (Williams, 1959a). Larger alkyl substituents (>C2) located at the alpha-or beta-position inhibit metabolism to CO 2 (Deisinger et al, 1994;Deuel, 1957;Albro, 1975) in which case there is either direct conjugation of the acid with glucuronic acid or omega-oxidation leading to diacid metabolites, which may be conjugated and excreted.…”
Section: Iii14 Metabolism Of Lactones Formed From Linear and Brancmentioning
confidence: 99%